Assessing Fixed Asset Write-Off Policy Effectiveness in Enhancing Regional Efficiency at Bappeda Riau Islands - Nurviani, Nanny; Tan, David; Situmeang, Ampuan (JURNAL LEGALITAS, 2025)
The management of Regional Assets (BMD) in Indonesia continues to face structural and procedural challenges, including inadequate inventory systems, insufficient human resource (HR) competencies, and weak inter-agency coordination. This study critically examines the effectiveness of the fixed asset write-off policy at the Regional Development Planning Agency (Bappeda) of Riau Islands Province in line with Permendagri No. 7 of 2024. Using an empirical legal research method through a sociological approach, the study captures field-based data to assess the practical implications of policy implementation. The findings reveal persistent inefficiencies in asset write-off procedures due to unclear Standard Operating Procedures (SOPs), lack of digital support systems, and low transparency. Additionally, institutional barriers such as limited administrative capacity and leadership gaps hinder policy execution. This study is the first empirical investigation of asset elimination practices in Bappeda Riau Islands, a region with distinctive archipelagic characteristics, thus offering significant academic and policy relevance. The study proposes actionable strategies, including the formation of a dedicated inventory team, HR capacity-building programs, and the enhancement of SOPs to streamline the write-off process. These solutions are expected to improve overall BMD governance, promote accountability, and support increased Regional Original Income (PAD). The research contributes a replicable model for regional governments, especially in geographically complex areas, to optimize asset management through evidence-based policy refinement.